Perancangan Sistem Pendukung Keputusan Penentuan Jenis Kosmetik Sesuai Dengan Jenis Kulit Wajah Dengan Menggunakan Metode Simple Additive Weighting (SAW) - Ika Triwahyuningsih; Lely Panca Andriyanto (shofanah Media Berkah, 2026)
The development of the cosmetics industry has led to an increase in the variety of products available on the market, which the consumers find challenging when selecting items that are appropriate for their facial skin type. Choosing the wrong product can lessen treatment effectiveness and cause quite dangerous side effects. This research intends to create a web-based DSS that identifies the appropriate cosmetics based on facial skin type by utilizing the SAW approach. The SAW method is utilized to assign weights and rank different products according to established criteria, thereby generating impartial recommendations. Findings from this study confirm that the system is capable deliver cosmetic product suggestions accurately and methodically, thus helping users to make more informed, effective, and safe choices.